2020
DOI: 10.1186/s12891-020-03353-8
|View full text |Cite
|
Sign up to set email alerts
|

Complications after surgical management of proximal humeral fractures: a systematic review of event terms and definitions

Abstract: Background: The most frequently used surgical procedures for treating a proximal humeral fracture (PHF) are plate osteosynthesis, nail osteosynthesis and arthroplasty. Evidence-based recommendations for an appropriate surgical procedure after PHF requires transparent and valid safety data. We performed a systematic review to examine reported terms and definitions of complications after surgically-treated PHFs. Methods: A literature search was conducted on PubMed, Cochrane Library, EMBASE, Scopus and WorldCat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In a systematic review, Alispahic et al summarized and sorted all the unfavorable events which were found in studies of proximal humerus fractures. In our study, the unfavorable events are presented in detail and in a differentiated manner, as Alispahic et al have published [ 2 ]. A total of 48 unfavorable events were seen in 27 (27.6%) patients in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review, Alispahic et al summarized and sorted all the unfavorable events which were found in studies of proximal humerus fractures. In our study, the unfavorable events are presented in detail and in a differentiated manner, as Alispahic et al have published [ 2 ]. A total of 48 unfavorable events were seen in 27 (27.6%) patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a recently published literature research by Alispahic et al the term “unfavorable events” (synonym: complication, adverse events) was used in our study [ 2 ]. The unfavorable events were divided into several groups as shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…While many terms are used in the literature to describe similar or associated events or conditions [ 6 , 7 ], some choices and decisions were made on what was perceived the most relevant terms that could be understood by the majority of clinicians (however not necessarily all stakeholders like the patients themselves). Some terms were conscientiously avoided.…”
Section: Discussionmentioning
confidence: 99%
“…We applied a similar methodological process for the development of the PHF CES as that used for ARCR [ 10 ] and SA [ 11 ]. Unfavorable event terms and definitions were identified from a systematic literature review including original articles published between 2010 and 2017, and grouped according to nine previously defined event groups [ 6 , 7 ]. An initial proposal for the PHF CES was drafted during a meeting of the authors, all members of the steering committee for this project.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation